Predisposing Factors of Ischemic Colitis: Data from 14 Years of Experience in a Single Center - Hyun Il Seo; Kyoo-ho Choi; Koon Hee Han; Sang Jin Lee; Jong Kyu Park; Young Don Kim; Gab Jin Cheon (Gastroenterology Research and Practice)
Background and Aims. While several case reports on ischemic colitis (IC) suggest the presence of predisposing causative factors, a few studies have investigated the predisposing factors in IC. This study aimed to identify the characteristics of patients with IC, particularly focusing on the predisposing factors. Methods. We conducted a single-center, retrospective analysis of 159 patients with IC. Clinical characteristics, laboratory data, endoscopic findings, and medical records were reviewed. Data were compared between groups of patients defined according to the predisposing factors. The predisposing factors are defined as temporary states or episodic events occurring within a week before the development of IC such as colonoscopy, enema, use of laxatives, heavy drinking, pancreatitis, shock, and burn. Results. Compared to the group of patients without predisposing factors of IC, the group of patients with predisposing factors was characterized by a relatively higher prevalence of male sex (56.9% versus 33.3%, p=0.005), younger age (60.9 ± 15.4 versus 67.2 ± 13.4 years, p=0.010), lower incidence of hypertension (43.1% versus 60.2%, p=0.044), and fewer risk factors (1.24 ± 1.18 versus 1.82 ± 1.22, p=0.005). Conclusions. Among men with predisposing factors, IC may develop even at a relatively younger age and in the absence of multiple risk factors, suggesting that predisposing factors may be involved in the pathogenesis of IC.